The Analysis of Presupposition in Inside Out Movie and Its Application in Teaching Speaking (Scripta : English Department Journal, 2023)
This research is aimed in analyzing types of presupposition used by the main character in the movie entitled Inside Out and describing the application of presupposition used by the main characters in Inside Out movie in teaching speaking. This research based on descriptive qualitative research. In this research the object is presupposition in movie entitled Inside Out. Source data is based from the dialogue of Inside Out movie. The researcher makes dialog in collecting the data and after that analyzed the dialog in one of procedure. The data analysis result in the table explaining all types there are 106 presuppositions containing 6 types of presupposition used by the main character. It consists of 49 (46%) for existential presupposition, 8 (8%) for factive presupposition, 6 (6%) lexical presupposition, 30 (28%) for structural presupposition, 4 (4%) for non-fative presupposition, 9 (8%) for counter-factual presupposition. The explanation of presupposition in Inside Out movie to explain teaching speaking for second grade students of Senior high School. The researcher to show the teachers to make interesting materials like a movie, it can make teacher good in teaching result
Keywords: Presupposition; Movie; Teaching speaking